FINANCIAL TRANSPARENCY IN THE KINGDOM OF SAUDI ARABIA AND ITS ROLE IN ACHIEVING ECONOMIC STABILITY - Makki Qasim Kuaiber (Scholar Express Journals, 2025)
From an accounting standpoint, transparency is a fundamental criterion. In its absence, accounting practices become arbitrary and unprofessional. A collection of accounting variables comprises financial transparency, specifically financial reporting, accounting standards, and auditing. Economic stability is the paramount objective of government policies across all nations, regardless of its attainment. The paramount element of economic stability is financial extrapolation. Consequently, the two are frequently interconnected and are mutually reinforcing. The research seeks to examine the effects of financial transparency on various economic indicators, the strategies to address the challenges encountered, and the insights gained from these experiences. The research produced several conclusions, the most significant of which was that achieving economic stability through financial transparency necessitates extensive strategic planning, to be executed incrementally. It necessitates absolute consistency and coherence between the institutions governing financial systems and those overseeing legislation. The Kingdom of Saudi Arabia has effectively surmounted considerable milestones on this journey. Keywords: financial transparency, economic stability, financial reporting, international accounting standards.
Keywords: considerable; economic stability; transparency